Research and Geoconservation of the Albian “Giant” Ammonites Collection in the Basque Coast UNESCO Global Geopark - Asier Hilario; Miguel Angel López-Horgue; Luis Miguel Agirrezabala (Geoconservation Research)
The Basque Coast UNESCO Global Geopark is known worldwide for its great thickness of Upper Cretaceous and Paleocene “flysch” formations. The K/Pg and P/E boundaries are among the most popular sites, together with the IUGS-ICS designated Selandian and Thanetian global stratotypes. However, an important section of the sea cliff outcrops is formed by an older and less known Albian “black flysch”. Its tectonic and sedimentological setting is related to the opening and spreading of the floor of the Bay of Biscay, which produced important environmental changes that triggered significant ammonoid bioevents, including the occurrence of large forms. Staff at the Basque Coast UNESCO Global Geopark (UGGp) and experts from the University of the Basque Country have carried out a research and geoconservation project based on a collection of more than 150 large-sized ammonites from a single fossil collector, who had accumulated them over 40 years from a particular location in the geopark cliffs. Integrative study of the sedimentary record and morphologies of the ammonoids collected through the section documents their distribution and evolution.